Primary visual cortical remapping in patients with inherited peripheral retinal degeneration - Ferreira, Sónia; Pereira, Andreia Carvalho; Quendera, Bruno; Reis, Aldina; Silva, Eduardo Duarte; Castelo-Branco, Miguel (NeuroImage clinical, 2017)
Human studies addressing the long-term effects of peripheral retinal degeneration on visual cortical function and structure are scarce. Here we investigated this question in patients with Retinitis Pigmentosa (RP), a genetic condition leading to peripheral visual degeneration. We acquired functional and anatomical magnetic resonance data from thirteen patients with different levels of visual loss and twenty-two healthy participants to study primary (V1) visual cortical retinotopic remapping and cortical thickness. We identified systematic visual field remapping in the absence of structural changes in the primary visual cortex of RP patients. Remapping consisted in a retinotopic eccentricity shift of central retinal inputs to more peripheral locations in V1. Importantly, this was associated with changes in visual experience, as assessed by the extent of the visual loss, with more constricted visual fields resulting in larger remapping. This pattern of remapping is consistent with expansion or shifting of neuronal receptive fields into the cortical regions with reduced retinal input. These data provide evidence for functional changes in V1 that are dependent on the magnitude of peripheral visual loss in RP, which may be explained by rapid cortical adaptation mechanisms or long-term cortical reorganization. This study highlights the importance of analyzing the retinal determinants of brain functional and structural alterations for future visual restoration approaches. •V1 functional remapping after genetically determined peripheral visual loss.•V1 functional remapping depends on the extent of peripheral retinal loss.•V1 retinotopic eccentricity shifts from central to more peripheral representations.•V1 remapping pattern differs from the one triggered by macular degeneration.•Retinotopic changes occur in the absence of structural alterations in V1.